Corrosion inhibition of iron in acidic solution by a green formulation derived from Nigella sativa L. (20th June 2016) - Chellouli, M.; Chebabe, D.; Dermaj, A.; Erramli, H.; Bettach, N.; Hajjaji, N.; Casaletto, M.P.; Cirrincione, C.; Privitera, A.; Srhiri, A.
Abstract: In this work the corrosion inhibition of iron in acidic solution by a formulation based on the oil extracted from the seeds of Nigella Sativa L. (labeled as FBN) was investigated by means of potentiodynamic polarization, electrochemical impedance spectroscopy and weight loss measurements. Results showed that the formulation acts as a good mixed type (cathodic/anodic) inhibitor. The dissolution rate decreased with the increase of the FBN concentration and the immersion time. An inhibition efficiency of 99% was reached for FBN concentration at 2500 ppm. Surface analysis of the samples was performed by Scanning Electron Microscopy coupled with chemical analysis (SEM-EDS) and X-ray Photoemission Spectroscopy (XPS). Results confirmed a good protective action of the FBN film on the iron substrate in acidic solution. The FBN formulation is a not toxic and environmentally safe product, as determined by acute toxicity tests, and can be fruitfully used for a sustainable conservation of iron-based artifacts.